2020
DOI: 10.1128/jb.00689-19
|View full text |Cite
|
Sign up to set email alerts
|

NOD2/c-Jun NH 2 -Terminal Kinase Triggers Mycoplasma ovipneumoniae-Induced Macrophage Autophagy

Abstract: Mycoplasma ovipneumoniae (M. ovipneumoniae) belongs to Mycoplasma, a genus containing the smallest self-replicating microorganisms, and causes infectious pleuropneumonia in goats and sheep. Nucleotide-binding oligomerization domain-containing protein (NOD2), an intracellular pattern recognition receptor, interacts with muramyl dipeptide (MDP) to recognize bacterial peptidoglycans and is involved in autophagy induction. However, there have been no reports about NOD recognition of mycoplasmas or about M. ovipneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…For example, a type III secretion system enables Shigella to avoid being detected by the host autophagic machinery [ 12 ]; Legionella pneumophila inhibits autophagy in mammalian cells [ 30 ]; and Staphylococcus aureus impairs autophagy for replication [ 28 , 31 ]. Similarly, Mycoplasma pneumoniae induced autophagy in mice [ 14 ], whereas Mycoplasma ovipneumoniae activated autophagy in RAW 264.7 cells [ 13 ]. In this study, to investigate autophagy, the ultramicrostructure of intracellular M. bovis was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a type III secretion system enables Shigella to avoid being detected by the host autophagic machinery [ 12 ]; Legionella pneumophila inhibits autophagy in mammalian cells [ 30 ]; and Staphylococcus aureus impairs autophagy for replication [ 28 , 31 ]. Similarly, Mycoplasma pneumoniae induced autophagy in mice [ 14 ], whereas Mycoplasma ovipneumoniae activated autophagy in RAW 264.7 cells [ 13 ]. In this study, to investigate autophagy, the ultramicrostructure of intracellular M. bovis was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For Mycoplasma species, which are the smallest prokaryotes capable of self-replication, autophagy has an important role in host–pathogen interactions. For example, Mycoplasma ovipneumoniae induced autophagy in macrophages in vitro [ 13 ]. Furthermore, autophagy had a critical role in stimulating the inflammatory response to Mycoplasma pneumoniae infections in mice [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, PTPN13 (PTP-BL) interacts with the Rho effector kinase protein kinase C-related kinase 2 ( PRK2 ) [53] and PRK2 has been demonstrated to have a role in cilia signaling [54] as well as regulation of the formation of apical junctions in bronchial epithelial cells [55]. Infection of a murine macrophage cell line with M. ovipneumoniae increases levels of nucleotide-binding oligomerization domain-containing 2 ( NOD2 ) and NOD2 along with activation of c -Jun NH2-terminal protein kinase ( JNK ) induces autophagy [56]. NOD2 interacts with RAC family small GPTase 1 ( Rac1 ) in membrane ruffles [57] and it has been suggested that Rho GTPases such as Rac1 regulate PRK2 activity during control of the cell cycle [58].…”
Section: Discussionmentioning
confidence: 99%
“…Infection of a murine macrophage cell line with M . ovipneumoniae increases levels of nucleotide-binding oligomerization domain-containing 2 ( NOD2 ) and NOD2 along with activation of c -Jun NH2-terminal protein kinase ( JNK ) induces autophagy [ 64 ]. NOD2 interacts with RAC family small GPTase 1 ( Rac1 ) in membrane ruffles [ 65 ] and it has been suggested that Rho GTPases such as Rac1 regulate PRK2 activity during control of the cell cycle [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, PTPN13 (PTP-BL) interacts with the Rho effector kinase protein kinase C-related kinase 2 (PRK2) [61] and PRK2 has been demonstrated to have a role in cilia signaling [62] as well as regulation of the formation of apical junctions in bronchial epithelial cells [63]. Infection of a murine macrophage cell line with M. ovipneumoniae increases levels of nucleotide-binding oligomerization domain-containing 2 (NOD2) and NOD2 along with activation of c-Jun NH2-terminal protein kinase (JNK) induces autophagy [64]. NOD2 interacts with RAC family small GPTase 1 (Rac1) in membrane ruffles [65] and it has been suggested that Rho GTPases such as Rac1 regulate PRK2 activity during control of the cell cycle [66].…”
Section: Plos Onementioning
confidence: 99%